Criticism of the use of memory as a learning resource during the 19th century in Chile - Lara, Jesús Moisés (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2019)
The purpose of this article is to elucidate how, during much of the 19th century, in Chile, the type of teaching that used to be transmitted began to be discussed, mainly that oriented towards the mechanic transfer of information, having as its sole purpose the development of memory to repeat concepts and phrases. For this reason, we carried out historiographic revisionism of primary sources from that time, in order to analyze the positions and criticisms against the clerical educational strategies, but also, to identify the pedagogical orientations that should begin to be adopted to generate changes in education.    Consequently, the contribution of this study is to demonstrate that the concern for the restructuring of the teaching-learning processes, focused on the development of higher-order skills in students, has an ongoing background throughout the nineteenth century.